Student Learning Result of Citizenship Education in Internet Learning Media with High Interpersonal Communication in High School Al-Azhar Medan - Ronald Hamonangan; Julaga Situmorang; Samsidar Tanjung (BIRCU, 2019)
the aim of this research is to get a student learning result of citizenship education in internet learning media with high interpersonal communication get solustion for problems about the teaching and learning process in Civics learning in this school, the researcher conducted a direct interview with the teacher who took care of the subjects to the location/ object of research, namely class XI teacher Al-Azhar High School Medan. This research was conducted at Al-Azhar High School Medan, in class XI, both for conducting instrument trials and conducting research. This research will be carried out in the even semester of 2018/2019 Academic Year, namely in April 2019, with the treatment given in 6 meetings. The result is Interpersonal communication is communication between communicator and communicant and Citizenship learning outcomes of students who have high interpersonal communication are higher than citizen ship learning outcomes of students who have low interpersonal communication.